2020
DOI: 10.3892/ijo.2020.5023
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA ZEB1‑AS1 predicts a poor prognosis and promotes cancer progression through the miR‑200a/ZEB1 signaling pathway in intrahepatic cholangiocarcinoma

Abstract: Emerging evidence suggests that long non-coding RNAs (lncRNAs) play pivotal roles in cancer progression, including in intrahepatic cholangiocarcinoma (IHCC). The overexpression of lncRNA ZEB1 antisense 1 (ZEB1-AS1) has been discovered in several types of cancer; however, the clinical significance and functional role of ZEB1-AS1 in IHCC have not yet been determined. In the present study, ZEB1-AS1 was found to be upregulated in IHCC cell lines and tissues. A high ZEB1-AS1 expression was associated with clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…However, the prognostic value of MVI in ICC patients remains unclear. In the report of Jiao et al [ 27 ] and Wang et al [ 28 ], the relationship between MVI and ICC patients was not significant. HU et al [ 14 ] showed that MVI was an important factor for RFS in ICC patients after surgery but not for OS.…”
Section: Discussionmentioning
confidence: 94%
“…However, the prognostic value of MVI in ICC patients remains unclear. In the report of Jiao et al [ 27 ] and Wang et al [ 28 ], the relationship between MVI and ICC patients was not significant. HU et al [ 14 ] showed that MVI was an important factor for RFS in ICC patients after surgery but not for OS.…”
Section: Discussionmentioning
confidence: 94%
“…ZEB1 is a classic epithelial-mesenchymal transition regulatory transcription factor. The complex arrangement of genes that mediate the transition from epithelial cells to mesenchymal cells has been proven to be related to the development and metastasis of CCA (34). Moreover, ZEB1 is an important regulator and potential prognostic factor in CCA (35).…”
Section: Analysis Of Frgs Regulated By Pdt In the Treatment Of Ccamentioning
confidence: 99%
“…Interestingly, ZEB1‐AS1 reinforces proliferation and metastasis of CCA in vivo, and its expression correlates with poor prognosis in patients. ( 59 ) LncRNA HEIH (HCC up‐regulated EZH2‐associated long noncoding RNA) is overexpressed in CCA. HEIH induces cell proliferation, migration, and invasion in vitro and promotes tumor growth in vivo .…”
Section: Lncrnas and Cancer‐associated Signaling Pathwaysmentioning
confidence: 99%